Design and implementation of aquaculture resource planning using underwater sensor wireless network. Issue 1 (1st January 2018) - Shetty, Shreema; Pai, Radhika M; Pai, Manohara M. M.
Abstract: Aquaculture is a globally fast-growing food sector, and its economic significance is increasing consistently. Currently, site selection for aquaculture is based on remote sensing and Geographic Information Systems (GIS), which provide infrastructure information. The information regarding environmental factors such as water properties are measured manually. There is a requirement for building a database on water properties at various river sites that are favourable for aquaculture. Underwater wireless sensor network (WSN) systems are being developed to measure various water parameters for aquaculture monitoring, and the mobility of sensor is considered for node deployment to increase the accuracy of measured water parameters. The present system integrates WSN nodes to extract the data and connect to cloud data server. A centralized database is created to store the information/data, which is analysed using clustering k -means algorithm. The proposed work presents an aquaculture resource planning (ARP), a SaaS (Software-as-a-Service) application; the users can access information using the application "Aquaward" and analyse various river sites that can be used for aquaculture development.